1221. Evaluation of the FilmArray® Global Fever Panel. (31st December 2020) - Helm, Jared R; Jones, Brian; Toxopeus, Corike; Rabiger, David S; Gurling, Mark; Veloz, Madeline; Kelley, Alex J; Jackson, Olivia; Burton, Marissa; Maxey, Sidney; Batty, Natalie; Wiltsie, Ashley; et al.
Abstract: Background: Acute Febrile Illness (AFI) is caused by a diverse set of pathogens. The FilmArray Global Fever (GF) Panel, developed by BioFire Defense in collaboration with the U.S. Department of Defense and NIAID, uses an automated, multiplex nested PCR system to evaluate whole blood samples for multiple pathogens simultaneously in under an hour. Methods: BioFire Defense conducted analytical performance studies to show sensitivity (LoD), inclusivity, and specificity (exclusivity), and a prospective clinical study to evaluate the positive percent agreement (PPA) and negative percent agreement (NPA) of the GF Panel. The results of these studies will be reported in two submissions to the US FDA. Results: The analytical performance demonstrated the ability to accurately detect multiple pathogens, including Category A biothreat pathogens. Eleven locations around the world tested 1, 865 specimens on the GF Panel. The rate of positive detections was 35% (652/1865), with Plasmodium spp. accounting for the majority of positives (53.4%, 348/652) and dengue virus the second most (40.5%, 264/652). Other detected pathogens include Leptospira spp., West Nile virus, Zika virus, Leishmania spp., Crimean-Congo hemorrhagic fever virus, and chikungunya virus. Twenty-eight (28) specimens had more than one detected pathogen (4.3% of positive specimens). Comparator testing consisted of in-house developed PCR assays followed by bidirectional sequencing. PPA between GF Panel and comparator testing ranged between 92.7-100%, and the NPA ranged between 99.3-100%. In all cases, discrepancies coincided with analytes that were near the limit of detection of the GF Panel and comparator assays. When the GF Panel result was compared to site-specific malaria testing, the PPA ranged between 94.7-100% and the NPA ranged between 43.3-100%. Analysis of the NPA suggests that the GF Panel is more sensitive than microscopy, producing "discrepancies" for this comparison. The wide range in NPA between sites could be due to variation in microscopy technique; the GF Panel eliminates such variation because it is fully automated. Conclusion: The results show that the FilmArray GF Panel could aid in rapid and actionable AFI diagnosis caused by multiple, sometimes co-occurring, pathogens. Disclosures: Jared R. Helm, PhD, BioFire Defense (Employee) Brian Jones, PhD, BioFire Defense, LLC (Employee, own stock) Corike Toxopeus, PhD, BioFire Defense, LLC. (Employee, stock owner) David S. Rabiger, PhD, BioFire Defense (Employee) Mark Gurling, PhD, BioFire Defense, LLC (Employee) Olivia Jackson, n/a, BioFire Defense (Employee) Marissa Burton, BS Biology, Biomerieux, Inc. (Shareholder) Cynthia Andjelic, PhD, BioFire Defense (Employee, Other Financial or Material Support, Own stocks) Cynthia L. Phillips, PhD, BioFire Defense (Employee, Scientific Research Study Investigator, Shareholder)BioFire Defense (Employee, Scientific Research Study Investigator, Shareholder)